A mixed‐methods systematic review of interventions to improve leadership competencies of managers supervising nurses. (1st November 2022) - Chen, Wenjun; Modanloo, Shokoufeh; Graham, Ian D.; Hu, Jiale; Lewis, Krystina B.; Gifford, Wendy
Abstract: Aim: This study aimed to synthesize evidence on interventions to improve leadership competencies of managers supervising nurses. Background: In recent years, numerous interventions have been developed to improve the leadership competencies of managers supervising nurses. However, researchers and nursing leaders are unclear about what aspects of interventions are effective for developing which competencies. Methods: We conducted a mixed‐methods systematic review following the Joanna Briggs Institute (JBI) approach for evidence synthesis. The Medline (Ovid), CINAHL, Embase, Scopus, Nursing and Allied Health Database were reviewed. Data extraction, quality appraisal and narrative synthesis were conducted in line with Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines. Results: A total of 69 studies (35 quantitative, 22 mixed methods, 12 qualitative) evaluating 68 interventions were included. Studies showed that interventions used modal activities such as lectures, group work and mentoring that generally had positive effects on improving leadership competencies such as supporting, developing and recognizing nurses. Opportunities to interact with peers increased managers' engagement in the interventions; however, many barriers existed for managers to use the competencies in practice including understaffing, insufficient time and lack of support from supervisors and staff. Conclusions: Leadership interventions were shown to have beneficial effects on developing different competencies. Managers predominately felt positive about participating in leadership interventions; however, they expressed many difficulties applying what they learned in practice. Implications for nursing management: Leadership interventions should include multimodal activities that give managers opportunities for interaction. When considering interventions for developing the leadership of managers, it is imperative to consider the practice environments for managers to be successful in applying the competencies they learned in practice.